2018
DOI: 10.1519/jsc.0000000000002204
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Relationship Between Coach and Athlete Perceptions of Training Intensity in Youth Sport

Abstract: To alleviate issues arising from the over/under prescription of training load, coaches must ensure that desired athlete responses to training are being achieved. The present study aimed to assess the level of agreement between the coach intended (pre-session) and observed (post-session) rating of perceived exertion (RPE), with athlete RPE during different training intensities (easy, moderate, hard). Coach intended RPE was taken prior to all field based training sessions over an 8 week in-season period. Followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 19 publications
1
37
1
Order By: Relevance
“…Banners (2017) conducted similar research monitoring 3024 training sessions in cross-country runners and noted that both male and female athletes tend to regress to moderate intensity training. Brink et al (2014) found weakmoderate correlations between sRPE predicted by coaches and that performed by young soccer athletes, while Scantlebury et al (2017a) found similar results regarding to the correlation of sRPE predicted by coaches and performed by young athletes of hockey, netball, rugby and soccer. On the other hand, Redkva et al (2016) investigated the correlation between sRPE predicted by coaches and performed by professional soccer athletes in physical, technical and tactical training, which demonstrated a moderate-strong correlation between coaches' prediction and athletes performing, and found no difference in the sRPE between coaches and athletes in any of training models investigated.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Banners (2017) conducted similar research monitoring 3024 training sessions in cross-country runners and noted that both male and female athletes tend to regress to moderate intensity training. Brink et al (2014) found weakmoderate correlations between sRPE predicted by coaches and that performed by young soccer athletes, while Scantlebury et al (2017a) found similar results regarding to the correlation of sRPE predicted by coaches and performed by young athletes of hockey, netball, rugby and soccer. On the other hand, Redkva et al (2016) investigated the correlation between sRPE predicted by coaches and performed by professional soccer athletes in physical, technical and tactical training, which demonstrated a moderate-strong correlation between coaches' prediction and athletes performing, and found no difference in the sRPE between coaches and athletes in any of training models investigated.…”
Section: Discussionmentioning
confidence: 70%
“…between ITL predicted by coaches and performed by athletes in sports, such as soccer (Brink et al, 2014, Redkva et al, 2016, Scantlebury et al, 2017a, rugby (Scantlebury et al, 2017a), tennis (Maurphy et al, 2017, netball (Scantlebury et al, 2017a), endurance running and cross-coutry running (Banners, 2017) , but there is a gap in the literature about same research in relation to other modalities, especially in relation to collective gymnastic. Modalities usually offered in fitness club such as indoor-cycling, as well as in non-athletes, active individuals who practice certain physical activity with other objectives that are not competitive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a 0-10 item scale tool and hypothesizes that the physiological responses of physical stress are followed by average perceived answers 14 . Results found using RPE scale have been effective in positive adaptations, both in high performance [15][16][17] and in the health scope 9,18,19 . RPE scale is also a simple and low-cost strategy to training load monitoring and control 20 .…”
Section: Introductionmentioning
confidence: 99%
“…However, for example, in the Sciences of Sport have been reporting a gap between what has been planned by the coach and that perceived by the athletes [15][16][17]21 . Brink, Frencken 21 have demonstrated that juvenile football players have perceived the training more intensely than what has been planned by the coach 21 , which can favour overtraining 17 .…”
Section: Introductionmentioning
confidence: 99%